Clinical and Mutation Description of the First Iranian Cohort of Infantile Inflammatory Bowel Disease: The Iranian Primary Immunodeficiency Registry (IPIDR). (19th May 2021) - Rahmani, Farzaneh; Rayzan, Elham; Rahmani, Mohammad Reza; Shahkarami, Sepideh; Zoghi, Samaneh; Rezaei, Arezoo; Aryan, Zahra; Najafi, Mehri; Rohlfs, Meino; Jeske, Tim; Aflatoonian, Majid; Chavoshzadeh, Zahra; et al.
ABSTRACT: We describe a cohort of 25 Iranian patients with infantile inflammatory bowel disease (IBD), 14 (56%) of whom had monogenic defects. After proper screening, patients were referred for whole exome sequencing (WES). Four patients had missense mutations in the IL10 RA, and one had a large deletion in the IL10 RB . Four patients had mutations in genes implicated in host:microbiome homeostasis, including TTC7A deficiency, and two patients with novel mutations in the TTC37 and NOX1 . We found a novel homozygous mutation in the SRP54 in a deceased patient and the heterozygous variant in his sibling with a milder phenotype. Three patients had combined immunodeficiency: one with ZAP-70 deficiency (T + B + NK − ), and two with atypical SCID due to mutations in RAG1 and LIG4 . One patient had a G6PC3 mutation without neutropenia. Eleven of the 14 patients with monogenic defects were results of consanguinity and only 4 of them were alive to this date.